INSTRUCTIONAL METHODS AS PREDICTORS OF TEACHERS’ JOB RETENTION IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (International Nexus Multidisciplinary Research Journal, 2025)
The study examined instructional methods as predictors of teachers’ job retention in public secondary schools in Anambra State. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The study was a correlational research design. The population of the study was 6,598 teachers in the 267 public secondary schools from the six education zones in Anambra State. The sample of 660 teachers was used for the study. Multistage sampling techniques comprising proportionate stratified and simple random sampling technique was used for the study. The instruments used for data collection was ‘Instructional Methods Questionnaire (IMQ) and Teachers’ Job Retention Questionnaire (TJRQ).’ The instruments were subjected to face and construct validation. The reliability of the instrument was done using Cronbach Alpha technique and the average coefficient values of 0.78 for IMQ and 0.82 for TJRQ were obtained and considered highly reliable and suitable for the study. Simple linear regression statistical tool was used for the study. The findings of the study revealed that principals’ monitoring method and feedback method positively and significantly predicted to teachers’ job retention in public secondary schools in Anambra State. The study therefore concluded that instructional methods are positive and significant predictors of teachers’ job retention in public secondary schools in Anambra State. Based on the findings, the study recommended that principals should constantly plan for teachers’ development through work orientation so as to inculcate in them the best teaching methodology needed in the teaching profession for continual improvement since it helped to sustain and retain teachers in public secondary schools in Anambra State.